2018
DOI: 10.1521/pedi_2017_31_307
|View full text |Cite
|
Sign up to set email alerts
|

Substance Misuse Is Associated With Increased Psychiatric Severity Among Treatment-Seeking Individuals With Borderline Personality Disorder

Abstract: Despite high prevalence rates of concurrent borderline personality disorder (BPD) and substance use disorders (SUDs), little is known about the impact of substance misuse on the presentation of BPD. Sixty-five individuals with BPD were assessed at intake and at 3- and 6-month follow-up. Assessment included validated instruments such as the Addiction Severity Index and the Revised Symptom Checklist (SCL-90-R). Over half (58.5%) of individuals entering treatment were currently misusing substances. Substance misu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 35 publications
0
10
1
1
Order By: Relevance
“…Despite this scale having been designed to measure phobic-related fears (e.g., travels away from home, public places, social interactions), individuals undergoing treatment for SUD may report fear of everyday situations that may represent potential risk of relapse. Thus, we do not find it surprising that phobic anxiety yielded the largest effect size when comparing SCL-90-R dimensions between clinical samples of substance users and nonusers (Heath et al, 2018).…”
Section: Discussioncontrasting
confidence: 60%
“…Despite this scale having been designed to measure phobic-related fears (e.g., travels away from home, public places, social interactions), individuals undergoing treatment for SUD may report fear of everyday situations that may represent potential risk of relapse. Thus, we do not find it surprising that phobic anxiety yielded the largest effect size when comparing SCL-90-R dimensions between clinical samples of substance users and nonusers (Heath et al, 2018).…”
Section: Discussioncontrasting
confidence: 60%
“…An epidemiological study reports that 78% of individuals with borderline personality disorder met the criteria for substance use disorder at least once in their lifetime (21). Individuals with group B personalities are known to show more impulsive behavior, greater mood swings, and more depressive symptoms (22). In a study on psychotic disorders, a significant proportion of patients (close to 30%) diagnosed with SMI displayed problematic personality traits associated with group B without necessarily being diagnosed with a personality disorder.…”
Section: Dual Disorders and Common Comorbiditiesmentioning
confidence: 99%
“…The results of the national epi-demiologic survey on alcohol and related conditions (NE-SARC) showed that 78.2% of individuals with BPD had lifelong criteria for a substance use disorder (SUD) (31). Heath et al also confirmed that individuals with BPD had a history of substance and alcohol abuse and also the severity of psychiatric symptoms such as depression, tension, anger, fatigue, and mood disorders were higher in these individuals and also they had legal problems and it was found that at the time of use, they had a high prevalence of NSSI including cuts (81.4%), strikes (36.7%), scratches, (33.3%) and burns (22.9%); overall, 50.9% of them perform various forms of NSSI (32).…”
Section: Discussionmentioning
confidence: 94%